In their own words: deception detection by victims and near victims of fraud - Junger, Marianne; Koning, Luka; Hartel, Pieter; Veldkamp, Bernard (Frontiers in Psychology, 2023)
Aim: Research on deception detection has usually been done in experimental settings in the laboratory. In contrast, the present research investigates deception detection by actual victims and near-victims of fraud, as reported in their own words. Materials and Methods: We used a nationally representative survey of fraud victims (N=2864) on 11 types of fraud. It uses reports from people who experienced an attempted or completed fraud, why they didn’t fall for it, or how it could have been prevented in hindsight. Qualitative information from near-victims (N=958) and actual victims (N=243) was analysed and categorized. Results: The main detection strategies that helped near-victims recognize fraud were 1) fraud knowledge (69%): these near-victims clearly recognized fraud, 2) noticing mistakes in fraudulent messages (27.9%), 3) distrust (26.1%), 4) rules and principles (11.7%) or 5) personal knowledge (7.1%). Strategies that are little used are contacting other people (5.5%), seeking information online (4%), contacting the fraudster (2.9%), or contacting their bank or credit card company (2.2%). Contacting the police occurred even less (0.2%). These strategies differed by type of fraud. We link the strategies of ‘noticing mistakes’ and ‘relying on personal knowledge’ to the theoretical concept of ‘individuating information’ and the concepts of ‘knowledge’ and ‘having rules and principles’ to ‘context-general information’ (Street, 2015). About 40% of the actual victims believed that their victimization might have been prevented by: 1) seeking information (25.2%), 2) paying more attention (18.9%), 3) a third party doing something (16.2%), 4) following safety rules or principles, like using a safer way of paying or trading (14.4%) or by 5) ‘simply not going along with it’ (10.8%). Most of these strategies are associated with a higher, not lower, likelihood of victimization. Conclusion: Knowledge of fraud is the best strategy to avoid fraud victimization. Therefore, a more proactive approach is needed to inform the public about fraud and attackers’ modus operandi, so that potential victims already have knowledge of fraud upon encountering it. Just providing information online will not suffice to protect online users.